HUBUNGAN ANTARA POLA MAKAN, STATUS GIZI, DAN KEBIASAAN MEROKOK DENGAN HIPERTENSI USIA PRODUKTIF DI DUSUN MERPATI DAN NIRWANA DESA SUNGAI KAKAP KABUPATEN KUBU RAYA - Pebriyandini, Tiya; Budiastutik, Indah; Saleh, Ismael (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2015)
Hypertension is a disease that results in high morbidity. This is caused by several factors such as, eating pattern, nutritional status, and smoking habits. Data from Health Department of Kabupaten Kubu Raya shows that the cases of hypertension in age group of 18-45 years old in 2011 were 21,2%. In 2012, the cases increased to 20,0%. These cases was higher than in Kabupaten Ketapang (9,7%). Even so, the national prevelance of hypertension cases reaches 25,8%.This study aimed to find out the correlation of eating pattern, nutritional status, smoking habit, and productive age hypertension in Dusun Merpati and Nirwana, Desa Sungai Kakap Kabupaten Kubu Raya. A cross sectional design was carried out in this study. The samples were selected by using quota sampling technique.The study revealed two findings. First, there was correlation of nutritional status (p value=0,000) and productive age hypertension. Second, there were no significant correlation of fat intake (p value=0,621), natrium intake (p value=0,369), smoking habit (p value=0,483), and productive age hypertension.As a result, Sungai Kakap public health center should reactivate the integrated assisted centre for productive age which has been set up, provide nutritional counseling, and conduct health programs which deal with nutritional status problem as a hypertension risk factor.Key words : eating pattern, nurtional status, smoking, age, hypertension, productive, Sungai Kakap Kubu Raya